Morphological studies on nepenthes species from Mount Pulai, Johor / Liliwirianis Nawi, Jumaat Adam and Hafiza A. Hamid - Nawi, Liliwirianis; Adam, Jumaat; A. Hamid, Hafiza (2009)
Nepenthes ampullaria, N. gracilis, N. rafflesiana and N. hookeriana were recorded in the study plots of Mount Pulai, Johore. Morphological studied showed that N. gracilis significantly different than the other species in morphological characters such as stem, leaves, leaf base, shape of upper pitcher, digestive glands on the inner pitcher wall of upper pitcher and on the inner wall of lower pitcher, type of digestive glands on the inner wall of upper and lower pitcher and peristome. Meanwhile N. ampullaria showed different characters in size of pitcher's lid, honey glands on the lower lid surface, inflorescence type, pedicel and pedicel extended by bract.